(untitled) (Jurnal Teknodik, 2024)
Augmented Reality can be defined as a real environment to which virtual objects are added with the integration of computer technology. This technology can provide interesting interactions for users because with this technology users can feel virtual objects as if they existed in a real environment. The research aims to design and produce Augmented Reality applications for network devices and find out the functionality of Augmented Reality network devices. The research is conducted at one of the vocational schools in Garut Regency, involving class X Multimedia. The research method is the Waterfall model providing a sequential or ordered software life flow approach starting from analysis, design, coding, and testing. Application testing data collection techniques use Black Box Testing and Network Device Augmented Reality Application Questionnaires. The results of the research are the product of Augmented Reality learning media for network devices equipped with supporting AR Books and the result of the Augmented Reality learning media application for network device testing which is 100% running well in 10 brands of cellphones. Therefore, it can be concluded that the application runs well based on functional aspects.